ICM Millennium Lectures on Games 2003
DOI: 10.1007/978-3-662-05219-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Network Topology and the Efficiency of Equilibrium

Abstract: Abstract. Different kinds of networks, such as transportation, communication, computer, and supply networks, are susceptible to similar kinds of inefficiencies. These arise when congestion externalities make the cost for each user depend on the other users' choice of routes. If each user chooses the least expensive (e.g., the fastest) route from the users' common point of origin to the common destination, the result may be Pareto inefficient in that an alternative choice of routes would reduce the costs for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(74 citation statements)
references
References 18 publications
6
68
0
Order By: Relevance
“…Since Milchtaich, [15], has shown that Braess' paradox does not occur in graphs with the serial-parallel structure, this corollary implies that as long as the network under consideration has a serial-parallel structure (for example, a network of parallel links), partially optimal routing always improves the overall network performance.…”
Section: Xomentioning
confidence: 99%
“…Since Milchtaich, [15], has shown that Braess' paradox does not occur in graphs with the serial-parallel structure, this corollary implies that as long as the network under consideration has a serial-parallel structure (for example, a network of parallel links), partially optimal routing always improves the overall network performance.…”
Section: Xomentioning
confidence: 99%
“…A s − t network has linearly independent paths if every s − t path contains at least one edge not belonging to any other s − t path 4 . Milchtaich [24,Proposition 5] proved that an undirected s − t network has linearly independent paths if and only if it is extension-parallel. Therefore, every (directed) extension-parallel network has linearly independent paths (see also [20,Theorem 1]).…”
Section: φ(σmentioning
confidence: 99%
“…Milchtaich [24] was the first to consider networks with linearly independent paths (under this name). Milchtaich proved that an undirected network has linearly independent paths if and only if it is extension-parallel.…”
Section: Introductionmentioning
confidence: 99%
“…Shows that the BP can not occur in purely series-parallel networks CK Theorem 12. Shows that "A two terminal network is series-parallel if and only if there is no embedded network having the WB configuration" (see Calvert [2] p14 and also Milchtaich [6]).…”
Section: Ck Theoremmentioning
confidence: 99%